Culture Differences of Indonesia Ethnic Minorities in Non-verbal Communication - Roslidah, Navila; Komara, Indra (Jurnal Studi Komunikasi, 2017)
Indonesia’s islands are homes to a diverse ethnic and religious group which have given rise to a large number of cultural practices. Despite their cultural wealth, Indonesian Ethnic Minorities have been facing many problems regarding their cultural heritage existence. Most of their problems occur due to the inharmonious relationship between them and the government. Therefore, cultural approach is needed as a means to bridge the gap between the indigenous groups with the government by socialising the cultural aspects in the academic environment. By doing so, people from academic environment can take part in preserving those cultures by joining some performances, learning to play traditional instruments and raising awareness in the society. As a result, people in academic environment will have a chance to show the government that those cultural heritages need to be preserved. At the same time, the Ethnic Minorities will understand that there are some people who are aware of the cultural values. In the end, the Ethnic Minorities can work hand in hand with the government in the cultural preservation and development. Keywords: Culture, communication, Ethnic Minorities